(untitled) (Bangladesh Journal of Neurosurgery, 2020)
Deep brain stimulation (DBS), a form of neuromodulation, is recognized as a therapeutic venture for the management of chronic pain, the evaluation and management of epilepsy, and the treatment of Parkinson’s disease and other movement disorders. Clinical investigators are conducting more trials for its further use in obsessive compulsive disorders (OCD), depression, and traumatic brain injury. It is imperative to address the ethical concerns of such innovative neurosurgical treatment and research with human experimentation in the respective arena. The term ‘neurosurgical ethics’ is a moral approach towards ethical problems emerging from our day to day neurosurgical practice and research as well as current and future innovation in the field. The review paper outlined the procedures of DBS, as currently used in therapeutic and experimental applications and to discuss the ethical concerns regarding this innovative procedure. Bang. J Neurosurgery 2020; 10(1): 92-96